Nowe stanowisko mchu Buxbaumia viridis w Puszczy Białowieskiej - Gawryś, Radosław; Szulc, Adam (Leśne Prace Badawcze, 2017)
This paper describes a new occurrence and location of the green shield moss Buxbaumia viridis (Moug. ex Lam. & DC.) Brid. ex Moug. & Nestl. in the Białowieża Forest. One sporophyte was found on a decaying spruce log. However, its existence and the present environmental conditions of the site are threatened by the death of spruce trees. The dying of the spruce trees is expected for the near future and will lead to altered shade conditions impacting on the shield moss.